Panorama dos estudos sobre percepção ambiental no Sudeste Brasileiro - Albuquerque, Suellen da Fonseca (Universidade Federal de São Carlos, 2025)
Environmental perception can be defined as the subjective interpretation of the environment, influenced by experiences, values, and sociocultural contexts, evolving from psychological roots to applications in environmental management and public policies. Considering this, the present study was proposed to investigate the main characteristics of research on environmental perception in the Southeast Region of Brazil through a qualitative-quantitative bibliographic review, conducted in the CAPES Periodicals database, focusing on scientific articles published between 2010 and 2025. Initially, 255 studies were identified, which, after successive screening stages by title, abstract, and full reading, resulted in 70 articles that comprise the analysis corpus. The analysis covered diverse themes, with qualitative-quantitative approaches that use questionnaires and interviews to capture attitudes and knowledge. The studied publics are concentrated in urban residents, students, and peripheral communities, while the prioritized environments are the metropolitan regions of São Paulo, Minas Gerais, and Rio de Janeiro, revealing an urban bias that underrepresents rural and coastal areas. An increase in publications was observed from 2015 onward, with a trend toward integrating environmental perception into participatory processes of municipal management and education for sustainability. The results reinforce the role of environmental perception as a subsidy to mitigate socio-environmental crises in the most urbanized region of the country, suggesting for future research comparative urban-rural analyses, mixed methods, and intercultural investigations for more inclusive policies, as well as an in-depth analysis of the results found by the analyzed studies.
An overview of environmental perception studies in Southeastern Brazil
Keywords: Revisão bibliográfica; Gestão socioambiental; Sustentabilidade; Participação social; Literature review; Socio-environmental management; Sustainability; Social participation; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA; 11. Cidades e Comunidades Sustentáveis; 4. Educação de Qualidade; 13. Ação contra a Mudança Global do Clima